Tackling Offshore Oil Spills to Achieve Maritime Security in Indonesia - Bulandari, Desty; Widodo; Yulianto, Bayu Asih (International Journal of Law and Society, 2022)
The increasing need for and investment in energy production from offshore oil and gas sources in Southeast Asian countries, including Indonesia, increases the risk of offshore oil spills. This research aims to describe Indonesia's maritime security regarding offshore oil spills. This research is qualitative with findings without statistical testing and collecting data sources through literature study. Data is analyzed through data condensation, data presentation, and drawing and verifying conclusions. The results of this study state that maritime security in the environmental sector, especially from pollution, is classified as the closest part to the marine safety dimension which aims to protect the marine environment and the blue economy which, among other things, is related to resource utilization. Oil spills can cause enormous economic losses and endanger ecological systems and community health. The shortcomings in handling the 2009 Montara case show that Indonesia's maritime security regarding offshore oil spills could have been more optimal.